Profil Penggunaan Insulin pada Pasien Diabetes Melitus Rawat Inap yang Mengalami Hipoglikemia - Firzatullah Ega Radyastra; Nanang Miftah Fajari; Franciscus Xaverius Hendriyono (Homeostasis, 2021)
Abstract: One of the factors that can cause hypoglycemia in diabetes mellitus patients who are hospitalized is the use of insulin therapy.The purpose of this study was to determine the profile of insulin use in inpatient DM patients who experienced hypoglycemia in the subspecialty clinic in the endocrine division of the Ratu Zalecha Martapura Regional Hospital. This research is descriptive with a cross-sectional approach. The technique of taking the subject uses a total sampling technique. There were 30 DM patients who experienced hypoglycemia with insulin therapy. The results showed that the age group that experienced the most hypoglycemia was 46 - 55 years (40%), had diabetes for ≥ 1 year (73.3%), and the most widely used regimen was basal - bolus (70%) then total the daily dose used at the baseline was 11.17 ± 4.47 units and the bolus portion was 20.83 ± 8.83 units. The conclusion of this study is that the most frequently used insulin regimen in inpatients with hypoglycemia is basal - bolus. Keyword:hypoglycemia, diabetes mellitus, insulin, inpatient, hospitalized. Abstrak: Salah satu faktor yang dapat menyebabkan kejadian hipoglikemia pada pasien DM rawat inap di rumah sakit adalah penggunaan terapi insulin. Tujuan penelitian ini untuk mengetahui profil penggunaan insulin pada pasien DM rawat inap yang mengalami hipoglikemia di Poli subspesialis penyakit dalam divisi endokrin RSUD Ratu Zalecha Martapura. Penelitian ini bersifat deskriptif dengan pendekatan cross-sectional. Teknik pengambilan subjek menggunakan teknik total sampling. Didapatkan 30 subjek pasien DM yang mengalami hipoglikemia dengan terapi insulin. Hasil penelitian menunjukkan kelompok umur yang paling banyak mengalami hipoglikemia adalah 46 – 55 tahun (40%), telah mengidap DM selama ≥ 1 tahun (73,3%), dan regimen yang paling banyak digunakan adalah basal – bolus (70%) lalu total dosis harian yang digunakan pada bagian basalnya 11.17 ± 4,47 unit dan bagian bolusnya 20,83 ± 8,83 unit. Kesimpulan penelitian ini adalah regimen insulin yang paling sering digunakan pada pasien DM rawat inap yang mengalami hipoglikemia adalah basal – bolus. Kata - kata kunci: hipoglikemia, diabetes melitus, insulin, rawat inap, rumah sakit.Abstract: One of the factors that can cause hypoglycemia in diabetes mellitus patients who are hospitalized is the use of insulin therapy. The purpose of this study was to determine the profile of insulin use in inpatient DM patients who experienced hypoglycemia in the subspecialty clinic in the endocrine division of the Ratu Zalecha Martapura Regional Hospital. This research is descriptive with a cross-sectional approach. The technique of taking the subject uses a total sampling technique. There were 30 DM patients who experienced hypoglycemia with insulin therapy. The results showed that the age group that experienced the most hypoglycemia was 46 - 55 years (40%), had diabetes for ≥ 1 year (73.3%), and the most widely used regimen was basal - bolus (70%) then total the daily dose used at the baseline was 11.17 ± 4.47 units and the bolus portion was 20.83 ± 8.83 units. The conclusion of this study is that the most frequently used insulin regimen in inpatients with hypoglycemia is basal - bolus. Keyword:hypoglycemia, diabetes mellitus, insulin, inpatient, hospitalized. Abstrak: Salah satu faktor yang dapat menyebabkan kejadian hipoglikemia pada pasien DM rawat inap di rumah sakit adalah penggunaan terapi insulin. Tujuan penelitian ini untuk mengetahui profil penggunaan insulin pada pasien DM rawat inap yang mengalami hipoglikemia di Poli subspesialis penyakit dalam divisi endokrin RSUD Ratu Zalecha Martapura. Penelitian ini bersifat deskriptif dengan pendekatan cross-sectional. Teknik pengambilan subjek menggunakan teknik total sampling. Didapatkan 30 subjek pasien DM yang mengalami hipoglikemia dengan terapi insulin. Hasil penelitian menunjukkan kelompok umur yang paling banyak mengalami hipoglikemia adalah 46 – 55 tahun (40%), telah mengidap DM selama ≥ 1 tahun (73,3%), dan regimen yang paling banyak digunakan adalah basal – bolus (70%) lalu total dosis harian yang digunakan pada bagian basalnya 11.17 ± 4,47 unit dan bagian bolusnya 20,83 ± 8,83 unit. Kesimpulan penelitian ini adalah regimen insulin yang paling sering digunakan pada pasien DM rawat inap yang mengalami hipoglikemia adalah basal – bolus. Kata - kata kunci: hipoglikemia, diabetes melitus, insulin, rawat inap, rumah sakit.